The Collaboration between Ministry of Trade and Sidoarjo's Industry and Trade Office (Disperindag) in Assisting Sidoarjo MSMEs Export Processed Food Products to Malaysia - Tsania HM, Arina Putri; Zudan Rosyidi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This research discuses the collaboration between the Ministry of Trade and the Industry and Trade Office of Sidoarjo Regency (Disperindag) in supporting the export readiness of Micro, Small, and Medium Enterprises (MSMEs), particularly those producing processed food products, to Malaysia. Using a descriptive qualitative approach, data were collected through interviews with government officials and MSME actors, as well as documentation and literature review. The study reveals that the collaboration is implemented through structured programs such as the Export Coaching Program, which includes business legality facilitation, export technical training, product curation, business matching, and export financing schemes. The Ministry of Trade provides policy support and international trade access, while Disperindag plays a local operational role in mentoring and monitoring MSMEs. One notable outcome of this collaboration is the successful delivery of product samples to potential buyers in Malaysia and the involvement of Sidoarjo MSMEs in business meetings with foreign partners. Also the important achievement was the marketing of Sidoarjo MSME products at DoMart Kuala Lumpur, Malaysia. Processed food was chosen because it has high durability and wide market potential. The main challenges faced by MSMEs include limited export knowledge, business legality, and production capacity. Through programs such as Export Coaching, MSMEs are coached to meet export standards and improve competitiveness. This research concludes that collaboration between local governments and MSME players is essential to strengthen the competitiveness of local products in the global market, as well as encourage regional economic growth through increased exports.